Diphosphoglycerate and Inosine Hexaphosphate Control of Oxygen Binding by Hemoglobin: A Theoretical Interpretation of Experimental Data - Ling, Gilbert N. (1970)
A theoretical equation is presented for the control of cooperative adsorption on proteins and other linear macromolecules by hormones, drugs, ATP, and other „cardinal adsorbents.” With reasonable accuracy, this equation describes quantitatively the control of oxygen binding to hemoglobin by 2,3-diphosphoglycerate and by inosine hexaphosphate.